ANTIDIABETIC, HYPOLIPIDEMIC, AND HISTOPATHOLOGICAL ANALYSIS OF ZINGERONE IN STREPTOZOTOCIN-INDUCED DIABETIC RATS - Jothi M, Arul; Cs, Parameswari; S, Vincent (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: This study assessed the effects of antidiabetic and hypolipidemic activity of Zingerone on STZ induced diabetic rats. Methods: In this study 30 Wistar male rats were divided into five groups: Group 1: Normals control receiving normal saline, Group 2: Diabetic control receiving single intraperitoneal administration of streptozotocin (STZ) (40 mg/kg body weight). Group 3: Five days after STZ administration, diabetic rats received zingerone (10 mg/kg body weight) orally for 30 days. Group 4: Five days after STZ administration, diabetic rats received metformin (50 mg/kg body weight) orally for 30 days and Group 5: Rats received zingerone alone (10 mg/kg body weight) orally for 30 days. Results: Zingerone treatment significantly reduced blood glucose level, Lipid profiles of serum, liver and kidney showed higher reduction in the levels of phospholipids (PL), triglycerides (TG) and free fatty acids (FFA) of zingerone treated diabetic rats than STZ-induced diabetic rats and Met-treated diabetic rats. In addition, zingerone treatment of STZ-rats was found to be effective in preserving the normal histological appearance of pancreatic islets, liver and kidney whereas the untreated diabetic rats exhibited pathological features. Conclusions: These findings substantiated the beneficial effects of zingerone in the treatment of diabetes through exhibiting hypolipidemic effects as well as restoring the function of several organs including the pancreas. Thus, zingerone may have the potential in managing the effects of diabetic complications in human subjects. Keywords: Diabetes, Streptozotocin, Ginger, Zingerone, Antidiabetic, Hypolipidaemic.